(untitled) (Revista Linhas, 2010)
O presente artigo tem como objetivo entender como o cristão-novo vem sendo tratado e de que maneira é representado em alguns livros didáticos que se remetem à História do Brasil, assim como entender a contribuição desse estudo no ensino de História, isto é, na construção do conhecimento histórico feita pelos alunos através dos mediadores culturais que possibilitam o ensino e a aprendizagem. Palavras-Chave: Cristãos-novos. Livros didáticos. Ensino e representação. Abstract The present article contemplates a discussion about the place the New Christians occupy in the school textbooks which make reference to Brazilian History beginning at the time of the colonization period, that are being published today in Brazil, as well as the contribution of these studies to History teaching, that is, in the historical knowledge construction carried out by the students through the cultural mediators that make teaching and learning possible. Keywords: New Christians. School textbooks. Teaching and representation.